Logistics maturity of the service industry – research results - Werner-Lewandowska, Karolina; Kosacka-Olejnik, Monika (Dojrzałość logistyczna przedsiębiorstw usługowych – wyniki badań, 2019)
The paper presents the results of research on the logistics maturity of the Polish service industry. The research goal of the article is to demonstrate the logistics maturity level of service enterprises. In the research, 2 000 Polish service enterprises were included, which represent various service sections according to the Polish code list of classification of business activities (hereafter: PKD). The companies under study were differentiated according to the company’s size, depending on the employment level. The subject of the research was the logistics tools used by the surveyed enterprises in areas of logistics activity such as warehouse management, transport management, supply chain management, supply and inventory management, and IT tools. To determine the logistics maturity level, the Logistic Maturity Model for Service Industry (hereafter: LMM4SI) was used, based on the assumption that the logistics maturity level of a service enterprise depends on the logistics engineering tools that were used
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 233-248
Keywords: logistics maturity; service enterprises; company logistics; logistics tools; dojrzałość logistyczna; przedsiębiorstwo usługowe; logistyka przedsiębiorstwa; narzędzia logistyczne